Ultrasonic Technique for Investigation of Residual Stresses in Cylindrical Forgings - Deputat, J.; Adamski, M.; Goljasz, J.; Kalisiewicz, J. (Engineering Transactions, 1993)
An ultrasonic method to examine statical stress fields in the subsurface layers of cylindrical steel forgings is described. The values of stresses are calculated from precise measurements of travel times of subsurface pulses longitudinal and transverse waves propagating in the direction of generating line. Suitable apparatus is described and some results of investigations of a shipborne shaft forging with favourable and unfavourable distributions of residual stresses are shown. Longitudinal and hoop stresses in a steel mill roll are also examined.